Screening for depression with the Edinburgh Postnatal Depression Scale and finding borderline personality disorder. (May 2019) - Judd, Fiona; Lorimer, Stephanie; Thomson, Richard H; Hay, Angela
Objective: The aim of the study was to explore the range of psychiatric diagnoses seen in pregnant women who score above the 'cut-off' on the Edinburgh Postnatal Depression Scale when this is used as a routine screening instrument in the antenatal period. Method: Subjects were all pregnant women referred to and seen by the Perinatal Consultation-Liaison Psychiatry Team of a tertiary public hospital over a 14-month period. Edinburgh Postnatal Depression Scale score at maternity 'booking-in' visit, demographic and clinical data were recorded and diagnoses were made according to Diagnostic and Statistical Manual of Mental Disorders (5th ed.) criteria following clinical interview(s) and review of documented past history. Data were analysed using descriptive statistics. Results: A total of 200 patients who had completed the Edinburgh Postnatal Depression Scale were seen for assessment; 86 (43%) scored ⩾13 on Edinburgh Postnatal Depression Scale. Of those scoring 13 or more on Edinburgh Postnatal Depression Scale, 22 (25.6%) had a depressive disorder. In total, 12 patients (14%) had an anxiety disorder, 14 (16.3%) had borderline personality disorder and 13 (15.1%) had a substance use disorder. An additional 23 women (26.7%) had two or more borderline personality traits. Conclusion: Psychiatric assessment of women who scored 13 or more on the Edinburgh Postnatal Depression Scale at routine antenatal screening identified a significant number with borderline personality disorder or borderline personality traits rather than depressive or anxiety disorders. Clinical Practice Guidelines note the importance of further assessment for all women who score 13 or more on the Edinburgh Postnatal Depression Scale. The findings here suggest that this assessment should be made by a clinician able to identify personality pathology and organise appropriate and timely interventions.